Forest cover change and ecosystem services of Katimok forest reserve, Baringo County, Kenya - Jebiwott, Alice; Ogendi, G M.; Makindi, Stanley Maingi; Esilaba, M O. (Springer, 2019)
Forests provide vital ecosystem services to communities living around them, contributing immensely to their livelihoods. Yet, these forests undergo land use changes that threaten the abundance and availability of ecosystem services. This chapter assesses forest cover changes and its impacts on the ecosystem services in Katimok Forest Reserve. Land use changes were quantified using Landsat satellite images for the years 1984, 2001, and 2015. Focus group discussions (FGDs) and household surveys were used to identify and characterize the changes in ecosystem services. Land cover maps were prepared using supervised classification method and post-classification technique was used to detect the changes in forest cover. The results indicate that in the period 1984–2001, there was a decline in dense forest by 4.9%. Open forestland and built-up area had increased by 4.3% and 0.6%, respectively within the same period. These changes led into the reduction and loss of ecosystem services such as loss of certain medicinal plants, decline in mushrooms, and habitat destruction. It is therefore important that the relevant forest resource management agencies formulate sustainable resource utilization options/strategies for the local communities to curb degradation of this life-supporting ecosystem.
Keywords: Ecosystem services; Land use; Forest cover change; Katimok Forest Reserve; Forest ecosystem